Stock Control in Automotive Industry with Simulation Utilization - Petra Vegnerová (Contemporary Economics)
At this time in economic environment there is the big trend of coming logistical chain, supply chain and supply chain management (SCM). SCM deals with material and information flows control, inventory management, demand forecast, production plan optimalization, distribution management etc. Nowadays for effective purchase, production and distribution plan and control in companies are utilized the simulation and simulation programmes. This paper deals with the simulation programme Witness and its utilization for finding of results real problems – simulation utilization for stocks solution in automotive industry. The model can be used for the determination of new delivery system of materials and for stocks reduction.